2018
DOI: 10.3389/fams.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Analysis of the Improving Sequence Effect for Monetary Rewards

Abstract: In this paper, we mathematically formalize the concept of improving sequence effect, which is one of the main anomalies of the discounted utility model [1]. The improving sequence effect implies a preference for a given sequence of outcomes, which increase over time, and has been empirically demonstrated for both monetary and nonmonetary results (hedonic experiences and health-related outputs). Nevertheless, to date, there is no mathematical treatment of this anomaly in the context of intertemporal choice, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Obviously, we have V(L) ϭ L, for r L ϭ r e ; V(L) Ͼ L, for r L Ͼ r e ; and V(L) Ͻ L, for r L Ͻ r e . Therefore, by using an exponential discount function, for r L Ͼ r e , the subjective present value of the loan V(L) is greater than its principal L. Rambaud, Torrecillas, and Garcia (2018) proved that this result applied to sequences in (increasing or decreasing) arithmetic progression. We found that it also applied to any loan repayment sequences.…”
Section: Hypothesesmentioning
confidence: 81%
“…Obviously, we have V(L) ϭ L, for r L ϭ r e ; V(L) Ͼ L, for r L Ͼ r e ; and V(L) Ͻ L, for r L Ͻ r e . Therefore, by using an exponential discount function, for r L Ͼ r e , the subjective present value of the loan V(L) is greater than its principal L. Rambaud, Torrecillas, and Garcia (2018) proved that this result applied to sequences in (increasing or decreasing) arithmetic progression. We found that it also applied to any loan repayment sequences.…”
Section: Hypothesesmentioning
confidence: 81%
“…For positive series of future rewards such as incomes, restaurant visits, leisure activities or other gains, the preference for improvement means that individuals prefer to start with the least attractive outcome and end with the most attractive outcome than the opposite, i.e., they prefer the rising sequence over the falling sequence adding up to the same total amount Prelec, 1991, 1993;Loewenstein and Sicherman, 1991;Gigliotti and Sopher, 1997;Thaler, 1999;Matsumoto et al, 2000;Guyse et al, 2002;Duffy and Smith, 2013;Duxbury et al, 2013). Likewise, for negative series of outcomes such as pains, annoying noise, discomfort or other losses, individuals prefer the falling sequence over the rising sequence (Ariely and Loewenstein, 2000;Ariely and Zauberman, 2000;Langer et al, 2005;Rambaud et al, 2018;Garcia et al, 2020). Some researchers examined human preferences for sequences with respect to loan repayment plans.…”
Section: Introductionmentioning
confidence: 99%